Sensitivity of stratospheric dynamics to uncertainty in O3 production. Issue 16 (29th August 2013) - Hsu, Juno; Prather, Michael J.; Bergmann, Dan; Cameron‐Smith, Philip
Abstract : [1] Some key photochemical uncertainties that cannot be readily eliminated by current observations translate into a range of stratospheric O3 abundances in the tens of percent. The uncertainty in O3 production due to that in the cross sections for O2 in the Hertzberg continuum is studied here with the NCAR Community Atmosphere Model, which allows for interactive climate and ozone chemistry. A min‐max range in the O2 cross sections of 30%, consistent with current uncertainties, changes O3 abundances in the lower tropical stratosphere by up to 30%, with a relatively smaller and opposite change above 30 hPa. Here we have systematically examined the changes in the time‐mean state, the seasonal cycle, and the interannual variability of the temperature and circulation associated with the ±30% change in O2 cross sections. This study points to the important role of O3 in the lower tropical stratosphere in determining the physical characteristics of the tropical tropopause layer. Reducing O2 cross sections by 30% increases ozone abundances which warms the lower stratosphere (60°S −60°N; 2 K maximum at equator) and lowers the tropopause height by 100–200 m (30°S –30°N). The large‐scale warming leads to enhanced stratification near the tropopause which reduces upward wave propagation everywhere except for high latitudes. The lowermost tropical stratosphere is better ventilated during austral winter. The annual cycle of ozone is amplified. The interannual variability of the winter stratospheric polar vortices also increases, but the mechanism involves wave‐mean flow interaction, and the exact role of ozone in it needs further investigation. Key Points: One uncertainty of ozone production is from O2 cross sections Tweaking O2 cross sections can change mean LMS temperature And result in dynamical changes in TTL and winter polar vortices